Political Marketing Mix in the Decision to Choose Pangkalpinang Mayoral Election 2024 - Yusuf Yusuf (Universitas Bangka Belitung, 2025)
Political marketing does not mean how to sell political parties or candidate pairs that are being promoted to voters, but something that focuses on how political parties or candidate pairs can create work programs related to current problems. The sustainability of regional development within five years requires testing of political marketing of the decision to elect the Mayor and Deputy Mayor of Pangkalpinang. The population of Pangkalpinang City, which has the right to vote and is also registered on the 2024 Permanent Voters List, amounting to 161,413 people, is the focus of this study. A sample of 399 was determined using the probability sampling method with a cluster sampling technique carried out in seven sub-districts in Pangkalpinang City. Data were collected using a quantitative questionnaire as a multiple linear regression analysis tool. The independent variable is the marketing mix associated with political marketing capacity, including political products, promotions, prices, and venues. In contrast, the decision to choose is a dependent variable. Regression analysis reveals a positive correlation between political products, political promotion, political price, and political place on voter decisions. The coefficient value of political products 0.402 indicates an influence of 40.2%, political promotion 0.255 indicates an influence of 25.5%, political price 0.163 indicates an influence of 16.3%, and political place 0.468 indicates an influence of 46.8% respectively on the decision-making process. The most significant regression analysis output is 0.468 on the shift of political place of political products, political promotion, and political price. This result shows that voters want to meet directly with voters to strengthen their opinions.